Site fidelity, reproductive behavior and investment in the Brazilian Reticulate Leaf Frog, Pithecopus ayeaye LUTZ, 1966 (Anura: Phyllomedusidae) - Borges, Marilia M. [UNESP]; Nali, Renato C. [UNESP]; Fiorillo, Bruno F.; Prado, Cynthia P. A. [UNESP] (Osterreichische Gesellschaft Herpetologie E V, 2018)
In this study, the authors describe the reproductive biology of a population of Pithecopus ayeaye LUTZ, 1966, a leaf-frog typical of the Cerrado of southeastern Brazil. Field expeditions were conducted monthly during the rainy season of 2013/2014. From 41 males captured, fourteen were recaptured from one to four times, up to 13 months apart. Some recaptures occurred close to the original calling site (< 2 m). The body size of males captured just once, and that of recaptured males were similar, suggesting that male chorus attendance and calling site fidelity are not influenced by male body size. However, males called mainly from or close to shrubs of Leandra sp., and all clutches were found inside folded leaves of this plant, which contain trichomes that could assist in fixing the eggs and protecting embryos until hatching. Thus, male attendance and fidelity to such locations may represent a high-quality oviposition site, increasing the likelihood of female choice. The reproductive investment of males (0.35 +/- 0.05 %; N = 14) and females (4.25 +/- 0.35 %; N = 3) was in general lower than that of other phyllomedusid species. This could be explained by (1) a comparatively long lifespan of P. ayeaye, which could represent more breeding opportunities for females; and (2) the occurrence of aggressive calls and physical combats, which could decrease the opportunities for multi-male spawning and sperm competition.
Keywords: Pithecopus ayeaye; reproduction; behavior; reproductive investment; site fidelity; natural history; Cerrado; Brazil; Amphibia: Anura: Phyllomedusidae